Merch y Mêl - Lewis, Caryl,LeBlond, Valériane (Y Lolfa, 2018)
Another charming, volume by Caryl Lewis and Valériane Leblond, following their success with Sgleinio'r Lleuad which was shortlisted for the 2015 Tir na n-Og Prize. Elsi lives with her grandmother, a beekeeper. By following the bees, and taking note of how the garden changes all through the year, Elsi comes to love each season.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books